Residues, dissipation, and dietary risk assessment of oxadixyl and cymoxanil in cucumber - Fan, Jiqiao; Li, Li (Frontiers in Environmental Science, 2022)
Oxadixyl and cymoxanil were widely used for controlling downy mildew in cucumber, however, there are few systematic researches on monitoring residue levels of these two pesticides in cucumber under the greenhouse and open field conditions. In this study, a simplified quick, easy, cheap, effective, rugged, and safe (QuEChERS) method was applied to analyze target compounds in cucumber. The average recoveries of oxadixyl and cymoxanil in cucumber was ranging from 96%-102%, with the relative standard deviations (RSDs) of 1.8%-4.0%. The limits of quantification (LOQs) for two pesticides were both 0.01 mg/kg. The dissipation of oxadixyl was in accordance with first-order kinetics equation with half-lives ranging from 1.8-3.1 days. On the pre-harvest interval (PHI) 3 or 5 days, the residue levels of oxadixyl in cucumber under open field were higher than those in greenhouse. Compared to oxadixyl, the cymoxanil degraded quickly, and its residues were below LOQ on the 3rd or 5th days after the last application. The terminal residues of oxadixyl and cymoxanil in the cucumber were both lower than the maximum residue limit (MRLs) in China. The risk quotient (RQ) used for dietary risk assessment were 1.8%-3.5% and 0.26%-0.51% for oxadixyl and cymoxanil, respectively. The results showed that the risks of these two pesticides used on cucumber at the experimental dosages were comparably acceptable for Chinese consumers of different gender and age groups. This study provides a reference data to use the oxadixyl and cymoxanil scientifically and rationally.